Answer this to be marked as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d6c/072639d282822c0137bf0608c9cf27fe.jpg)
Answers
Answered by
1
as easy as 123...........
hope this helps!!!!!!!!!!
.
hope this helps!!!!!!!!!!
.
Attachments:
![](https://hi-static.z-dn.net/files/d90/c4798257da28e07a613027d66613f8a6.jpg)
lax4:
simple
Answered by
1
extend bc to ad
let bc meet ad at E
angle a + angle c =angle CED
now in triangle in ced
angle ced + angle x =angle b
so
angle x = angle b - angle ced
that is
x = b - a - c
let bc meet ad at E
angle a + angle c =angle CED
now in triangle in ced
angle ced + angle x =angle b
so
angle x = angle b - angle ced
that is
x = b - a - c
Similar questions